PROPOSED SANCTIONS FOR PROFESSIONALISM LAPSES BY THE STUDENTS AND THE STAFF IN TWO PAKISTANI MEDICAL COLLEGES: Proposed Sanctions For Professionalism Lapses - Shukr, Irfan; Choudry, Abeera; Safdar, Aqeel (Pakistan Armed Forces Medical Journal, 2017)
Objective: To determine the proposed level of sanctions by the students and the staff for professionalism lapses related to academic integrity in two Pakistani medical colleges.Study Design: Cross sectional study.Place and Duration of Study: Private Medical Colleges in the year 2013.Material and Methods: A stratified sample of 520 students, and 60 faculty members were invited to participate in this cross sectional study. A validated and customized version of Dundee Poly-professional Inventory–1 for use in Pakistani medical schools was used. The students were asked to indicate the appropriate level of sanctions (1-10) that should apply for the first time offence without circumstances that lessen the gravity of the offence.Results: The response rate of students and faculty was 92%, and 62% respectively. There was statistically significant difference between the students and the faculty (p